PENGARUH NPL DAN BOPO TERHADAP ROE PADA PT. BANK RAKYAT INDONESIA, Tbk PERIODE 2011-2018 - Rosita, Dian; Simamora, Saur C (Feb Universitas Dirgantara Marsekal Suryadarma, 2020)
This research was conducted to examine the effect of Net Performing Loan (NPL) and Operational Costs on Operating Income (BOPO) on Return On Equity (ROE) in PT. Rakyat Indonesia Bank, for theperiod 2011-2018 period. The sampling technique in this study is 32 quarterly data obtained from the bank’spublished financial statements for the period 2011-2018. The analysis technique used is multiple regression analysis. Because the data used are secondary data, then to determine the accuracy of the model it is necessary to test some basic assumptions, linearregression analysis, hypothesis testing and coefficient of determination. Testing the basic assumptions usedin this study include the normality test, linearity test and homogeneity test. While the linear regressionanalysis includes multiple linear regression and classical assumption tests (multicollinearity, autocorrelationand heterokedastisitas) and hypothesis testing which includes t test and f test. The dependent variable in this study is ROE while the independent variables are NPL and BOPO. The results of tis study, among others, indicate that the R square is 0,519 or 51,9 %, the NPL and BOPOvariables have a partial effect on ROE as well as the NPL and BOPO variables also have a simultaneouseffect against ROE. Based on the results of the above research, it is suggested to be able to add knowledgeabout NPL and BOPO to the level of ROE so that it can be input into research that is in line with this.Keywords: NPL, BOPO dan ROE